1995
DOI: 10.1021/bi00038a046
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes Reconstituted in Vitro on Mouse Mammary Tumor Virus B Region DNA Occupy Multiple Translational and Rotational Frames

Abstract: The mouse mammary tumor virus acquires a highly reproducible chromatin structure when integrated into cellular DNA. Previous studies have suggested that the LTR is arranged as a series of six phased nucleosomes, that occupy specific positions on the LTR. On the basis of nucleosome reconstitution studies using DNA from the B region of the LTR, it has been argued that this sequence directs a uniquely positioned nucleosome. Here we demonstrate in vitro that reconstituted B region nucleosomes adopt at least five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Each family contains a group of nucleosomes in a frequency-biased distribution among a set of available translational frames. These findings were reinforced by the observation that nucleosomes reconstituted in vitro on short fragments of LTR DNA demonstrated both translational and rotational complexity (38). An alternate view (34) is that each position represents a single core, with a unique translational and rotational position.…”
Section: The Mmtv Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Each family contains a group of nucleosomes in a frequency-biased distribution among a set of available translational frames. These findings were reinforced by the observation that nucleosomes reconstituted in vitro on short fragments of LTR DNA demonstrated both translational and rotational complexity (38). An alternate view (34) is that each position represents a single core, with a unique translational and rotational position.…”
Section: The Mmtv Modelmentioning
confidence: 98%
“…This interpretation derives primarily from the observation of 10-bp ladders over the B region when lightly digested with DNase I in vivo. Roberts et al (38) observed clear 10-bp periodicities for an in vitro reconstitute that contained five different core positions, demonstrating the difficulty of using this criterion for determination of high resolution positions. Similar data from several other systems (summarized in Fragoso et al (33)) is also consistent with multiply positioned cores within families.…”
Section: The Mmtv Modelmentioning
confidence: 99%
“…DNA cleavage at every 10 bases by hydroxyl radicals reflects the periodic exposure and protection of the DNA backbone to solvent when DNA is wrapped over the histone octamer in the nucleosome core particle; this periodic cleavage is reduced or absent in free linker DNA (45,46). Thus, the cleavage pattern of the top strand shows that one border of the N1 nucleosome is located at ϳ50 bases from the left end of the DNA fragment (Fig.…”
Section: Nurf Moves a Positioned Nucleosome Within Seconds-tomentioning
confidence: 99%
“…1C). Given that the edge of a nucleosome is not always precisely defined by the hydroxyl radical cleavage pattern, we localized the position of the nucleosome pseudo-dyad, and thus the position of the nucleosome, by the increased helical periodicity of the DNA adjacent to the dyad (11-12 bp/turn), in comparison with the periodicity of peripheral regions (10 bp/turn) (45,46). Accordingly, consecutive cleavage maxima spanning 22-23 bases were found to be centered at bases 122 (N1), 112 (N2), and 102 (N3) on the top strand (Fig.…”
Section: Nurf Moves a Positioned Nucleosome Within Seconds-tomentioning
confidence: 99%
“…The activity of the TATA box element in the MMTV long terminal repeat (LTR) is high in in vitro systems (53); however, the basal level of this promoter in the context of the integrated provirus is very low, presumably due to general repression by chromatin proteins (3). Ample evidence suggests that the MMTV LTR is occupied by an array of six nucleosomes (16,70) that have compositions typical of eukaryotic chromatin (two each of histones H2A, H2B, H3, and H4) (72). Chromatin structure has been shown to change in the presence of glucocorticoids (69,70,86,98), and it is believed that this change allows promoter activation through the binding of transcriptional activators such as NF-1 and Oct-1 and the basal transcription apparatus (20,48).…”
mentioning
confidence: 99%